Lessons Learned about High-Risk Pregnancy on the Frequency of Antenatal Care at the Cilodong Community Health Center Depok City - Ella Nurlelawati (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
Most of the deaths of pregnant women are caused by obstetric complications, which are often unpredictable during pregnancy or childbirth. The high maternal mortality rate in Indonesia is mostly caused by bleeding, eclampsia, infection, abortion, or obstructed labor. Very few maternal deaths are caused by diseases that worsen with pregnancy, such as heart disease and chronic infections. The thing that is very concerning is that out of the total cases of postpartum hemorrhage, only 7 people perform ANC regularly. The purpose of this study was to determine the relationship between the frequency of ANC and the knowledge of pregnant women about high-risk pregnancies at the Cilodong Health Center in Depok City in 2020. This research is a type of analytical research with a cross-sectional approach. The results of the analysis using the SPSS 12.0 program obtained a chi square value of 18.633 with a probability of 0.000, while the Chi square table at df = 3 was 7.81. The frequency of ANC has a significant relationship with knowledge about high-risk pregnancies at the Cilodong Community Health Center, Depok City, in 2018.